Buruli Ulcer: Treatment Challenges at Three Centres in Ghana. (29th November 2012) - Agbenorku, Pius; Donwi, Isaac K.; Kuadzi, Pawson; Saunderson, Paul
Abstract : Aims. This retrospective study was to identify some challenges in the treatment of Buruli ulcer (BU) and present a proposed treatment regime. Materials and Methods. Information from patients medical records, hospital database, and follow-up findings on BU treatment procedures from 1994 to 1998 and from 2004 to 2007 at three research sites in Ghana were reviewed to determine the treatment challenges encountered. Data needed were recorded and analyzed, and results presented using SPSS version 17.0. Results. A total of 489 BU patients information was selected for the study. A majority (56.90%, n = 278 ) of the patients were children (0–14 years), with a mean age of 12.8 years. Significant challenges in BU treatment in Ghana identified included sequelae (P = 0.041 ), delayed treatment (P = 0.012 ), and high treatment cost (P = 0.044 ). Duration of hospital stay was clearly correlated with the time spent at home prior to admission; spearman's rank correlation coefficient was 0.72 (95% CI 0.42–0.87). Conclusion. Delays in seeking treatment among BU patients were the main factor which resulted in most of the other factors contributing to the challenges in treatment. A combination of psychosocial and biomedical approach was proposed as holistic method to alleviate the challenges in BU treatment.